A new orb-weaving spider from the Argentinean flooding pampas grasses: Aculepeira morenoae new species (Araneae, Araneidae) - Rubio, Gonzalo D.; Izquierdo, Matías A.; Piacentini, Luis N. (Zootaxa, 2013)
A new species of the orb-weaving spider genus Aculepeira Chamberling & Ivie 1942, A. morenoae new species, is de-scribed and illustrated based on male and female specimens from the Argentinean natural flooding pampas grasses.